Bio-clinical and psycho-social nursing practice. An experimental research in an Intensive Coronary Care Unit - Foà, Chiara; La Sala, Rachele; Artioli, Giovanna; Tonarelli, Annalisa; Sarli, Leopoldo; Mancini, Tiziana (Acta Biomedica Atenei Parmensis, 2015)
Background and aim: The literature on patients with cardiovascular disease emphasizes the importance of providing a bio-medical and a psycho-social nursing care during the three phases of the nursing process (acceptance, assistance, education). How is his multidimensional nursing approach actually used during nursing practice? The present study aimed to evaluate the effects of a nursing educational training and it was finalized to implement a multidimensional care practice of nurses working in Intensive Coronary Care Unit (I.C.C.U.). Method: The entire nursing staff of the I.C.C.U of Parma Hospital (N = 17) took part in the research and it has been randomized in two subgroups. A group of 9 nurses participated as experimental group. They filled up a semi-structured questionnaire investigating the bio-clinical and psycho-social nursing activities, before (pre-test, time 1) and after (post-test, time 2) a professional training. 8 nurses participated as control group. They filled out the same questionnaire (at the time 1 and 2), but they did not participate at the professional training. Results: Results indicated how the nursing practice was more related to the bio-clinical (e.g. blood pressure) than to the psycho-social (e.g. mood) activities at the time 1. After the professional training (time 2), only the experimental group changed its professional practice, by integrating the bio-medical with the psycho-social nursing. Conclusions: The data showed the importance to promote a multidimensional educational path for nurses that assess the impact of the professional training on the professional practice, in order to improve the quality of care delivered to patients affected by cardiovascular disease.